From Handwriting to Footprinting Text and Heritage in the Age of Climate Crisis - Baillot, Anne (Open Book Publishers, 2023)
How do we currently preserve and access texts, and will our current methods be sustainable in the future? In From Handwriting to Footprinting, Anne Baillot seeks to answer this question by offering a detailed analysis of the methods that enable access to textual materials, in particular, access to books of literary significance. Baillot marshals her considerable expertise in the field of digital humanities to establish a philological overview of the changing boundaries of 'access' to literary heritage over centuries, deconstructing the western tradition of archiving and how it has led to current digital dissemination practices. Rigorously examining the negative environmental impact of digital publishing and archiving, Baillot proposes an alternative model of preservation and dissemination which reconciles fundamental traditions with the values of social responsibility and sustainability in an era of climate crisis. Integrating historical, archival and environmental perspectives, From Handwriting to Footprinting illuminates the impact that digitisation has had on the dissemination and preservation of textual heritage and reflects on what its future may hold. It is invaluable reading for anyone interested in textual history from a linguistic or philological perspective, as well as those working on publishing, archival and infrastructure projects that require the storing and long-term preservation of texts, or who want to know how to develop a more mindful attachment to digitised material.